Gw2.1, a new allele of GW2, improves grain weight and grain yield in rice. (December 2022) - Huang, Jinpeng; Chen, Zhiming; Lin, Jiajia; Guan, Binbin; Chen, Jinwen; Zhang, Zesen; Chen, Fangyu; Jiang, Liangrong; Zheng, Jingsheng; Wang, Tiansheng; Chen, Huiqing; Xie, Wangyou; et al.
Abstract: Grain weight is an important characteristic of grain shape and a key contributing factor to the grain yield in rice. Here, we report that gw2.1, a new allele of the Grain Width and Weight 2 ( GW2 ) gene, regulates grain size and grain weight. A single nucleotide substitution in the coding sequence (CDS) of gw2.1 resulted in the change of glutamate to lysine (E128K) in GW2.1 protein. Complementation tests and GW2 overexpression experiments demonstrated that the missense mutation in gw2.1 was responsible for the phenotype of enlarged grain size in the mutant line jf42 . The large grain trait of the near-isogenic line NIL- gw2.1 was found to result from increased cell proliferation during flower development. Meanwhile, NIL- gw2.1 was shown to increase grain yield without compromising the grain quality. The GW2 protein was localized to the cell nucleus and membrane, and interacted with CHB705, a subunit of the chromatin remodeling complex. Finally, the F1 hybrids from crosses of NIL- gw2.1 with 7 cytoplasmic male-sterile lines exhibited large grains and desirable grain appearance. Thus, gw2.1 is a promising allele that could be applied to improve grain yield and grain appearance in rice. Availability of data and materials: The datasets generated and/or analyzed in the study are available from the corresponding author on reasonable request. Highlights: gw2.1 was a new GW2 allele that influences grain size and grain weight. NIL- gw2.1 exhibits a larger grain size and increased grain weight without reducing rice appearance quality. gw2.1 affects glume shape by regulating cell proliferation. GW2 is located in the cell nucleus and membrane and interacts with CHB705. The application of gw2.1 improves grain yield and appearance quality in hybrid rice combinations.